Modeling of the kinetics of polymerization of dimethacrylates. The kinetic constants vs. termination mechanism - Andrzejewska, E.; Bogucki, M. B.; Andrzejewski, M.; Tymińska, B. (Polimery, 2022)
Summary - Diethylene glycol dimethacrylate was selected as a model multifunctional monomer to study the kinetics of polymerization under varying temperature and photoinitiator (2,2-dimethoxy-2-phenylacetophenone (DMPA)) concentration conditions. Three kinetic models: I - monomolecular termination, II - bimolecular termination, and III - mixed type termination, were used to describe polymerization rates under nonsteady-state conditions (after initiation has been discontinued) (eqns. 10, 11 and 12, resp.). Isothermal DSC was used to measure the polymerization rate as a function of time. For model II, the ratio was determined of the bimolecular termination rate constant to the propagation rate constant; for model I, the monomolecular termination rate constant; and, for model III, both constants The individual constants were established by additionally using steady-state equations with termination assumed to be mono- or bimolecular or mixed type (Figs. 2-7). Two-stage statistical analysis was applied to find the model that best reproduced the experimental data. For each model, the kinetic constants were established in relation to the degree of conversion of double bonds. Polymerization is discussed in terms of each model applied. The assumptions underlying model II are consistent with those conventionally applied to establish the kinetic constants; the relationship established as a function of the degree of conversion are consistent with those reported in the literature. Model I assumptions, viz., monomolecular termination, do not affect the qualitative pattern of relations between the constants and degree of conversion. The mixed-type model (III) yielded results that tied up the relationship attained with model I and II and also described the trapping of ma-croradicals and the reaction of two macroradicals with each other under the experimental conditions. The present results show monomolecular reaction to be the essential mechanism of termination in the polymerization of milti-functional monomers under the experimental conditions applied.